Pengaruh Kompensasi, Stress Kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan pada PT. Stara Bumi Surya - David David; Purnama Yanti Purba; Yola Yola; Ferry Leonardo; Elfina Okto Posmaida Damanik (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study is to investigate and evaluate how PT. Stara Bumi Surya employees perform in relation to pay,stress at work, and work discipline. The basis of this research includes the phenomena of low compensation offered by firms, the burden of working too much, the employees who frequently arrive late, and the number of employees whoquit annually from 2018 to 2022. Explanatory research using a quantitative descriptive research design is the researchmethodology employed. The participants in the study are PT. Stara Bumi Surya employees. Saturated sampling was themethod utilized for 68 responders. Multiple linear regression analysis is the technique utilized for data analysis. Thestudy's findings demonstrate that work stress significantly impairs employee performance, remuneration significantly enhances employee performance, and work discipline significantly enhances employee performance at PT StaraBumi Surya. Work discipline, workplace stress, and pay all have positive and significant effects simultaneously.